Covalent capture of oriented calix[6]arene rotaxanes by a metal-free active template approach. Issue 45 (22nd May 2017) - Orlandini, Guido; Ragazzon, Giulio; Zanichelli, Valeria; Secchi, Andrea; Silvi, Serena; Venturi, Margherita; Arduini, Arturo; Credi, Alberto
Abstract : A rotaxane with predetermined orientation of its nonsymmetric components is obtained by a rim-selective active template effect exerted by a calix[6]arene. Abstract : We describe the active template effect of a calix[6]arene host towards the alkylation of a complexed pyridylpyridinium guest. The acceleration of the reaction within the cavity is significant and rim-selective, enabling the efficient preparation of rotaxanes with full control of the mutual orientation of their nonsymmetric components.